Evaluation of predictive value of olfactory dysfunction, as a screening tool for COVID‐19 - Romero‐Gameros, Carlos Alfonso (Laryngoscope Investig Otolaryngol, 2020)
OBJECTIVES: At the end of 2019, SARS‐CoV‐2 was identified, the one responsible for the COVID‐19 disease. Between a 5.1% and a 98% of COVID‐19 patients present some form of alteration in their sense of smell. The objective of this study is to determine the diagnostic yield of the smell dysfunction as screening tool for COVID‐19. METHODS: Cross‐sectional, observational, and pro‐elective study was performed in a tertiary care hospital from May 25th to June 30th, 2020. One hundred and thirty‐nine patients were included in the study. Demographic characteristics were collected from anamnesis. A Self‐Perception Questionnaire and psychophysical olfactory test (POT) were applied to all participants. The presence of SARS‐CoV2, was detected by RT‐PCR methods. RESULTS: 51.7% of patients were SARS‐CoV‐2 positive. A sensitivity of 50% was obtained for the self‐perception questionnaire as a screening tool for SARS‐CoV2, with a specificity of 80.59%. The positive predictive value (PPV) was of 73.46%, the negative predictive value (NPV) was of 60%. The POT as a screening tool had a PPV of 82.35%, a NPV of 52.45%, a LR+ of 4.34, a LR‐ 0.84. The combination of anosmia (according to the POT) plus cough and asthenia got an OR of 8.25 for the SARS CoV‐2 infection. CONCLUSION: There is a strong association between olfactory dysfunction and COVID‐19. However, it is not really efficient in the screening of SARS‐CoV‐2 infection and thus, they should not be considered as a single diagnostic instrument. LEVEL OF EVIDENCE: 4.